A REVIEW ON BIOGENIC PROPERTIES OF STEM BARK OF TERMINALIA ARJUNA: AN UPDATE - Gaikwad, Dinanath; Jadhav, Namdeo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The traditional and alternative systems of medicine have been resulting more than 85% of the drugs from a plant source. Terminalia arjuna (T. arjuna) stem bark contain glycosides, ample quantities of flavonoids, tannins, and minerals. Flavonoids have been identified to exert antioxidant, anti-inflammatory, and lipid-lowering effects while glycosides are cardiotonic, thus making T. arjuna bark inimitable. In this review, an attempt has been made to discuss various aspects of its ethnomedical, phytochemical, pharmacological, and clinical relevance to various ailments condition. Available data from PubMed, Science Direct, and Web of Science were reviewed. Review articles, case reports, and clinical studies were included. Ultimately, after the elimination of repetitive information, 60 articles were identified. Most of the studies, both experimental and clinical, have suggested that T. arjuna bark possesses anti‑ischemic, antioxidant, and hypolipidemic activity. Its useful phytoconstituents are triterpenoids, flavonoids, glycosides, tannins, phenolics, and arjunolic acid. Experimental studies have revealed that T. arjuna bark exerting significant cardioprotective and as potent antioxidant activity. So far, no serious side effects have been reported with T. arjuna bark therapy. However, its long‑term safety still remains to be elucidated. T. arjuna bark has been found quite useful as cardioprotective agent. The present comprehensive update review is, therefore, an effort to give detailed information on T. arjuna stem bark for overall management of several ailments.